Evaluation of alkali–silica reaction in concretes with natural rice husk ash using optical microscopy - Zerbino, Raúl (2014)
The use of rice husk ash as a supplementary cementing material is of great interest to many developing countries where rice production is in abundance. A highly reactive pozzolan is obtained when rice husk ash is burnt under controlled conditions. Previous work showed that it is possible to use residual rice husk ash ‘‘as nature’’ (natural rice husk ash). Nevertheless, it was observed that the incorporation of natural rice husk ash implies risks of expansions and mechanical degradation due to the reactions with alkalis. Based on the performance of slab prototypes placed outdoors during more than 3 years, this work analyzes the causes and the damage processes involved in the development of expansions in presence of natural rice husk ash. Optical microscopy observations on thin sections; crack patterns of the slabs and the strength and surface strain evolution along the time were evaluated. Visual and microscope observations showed clear signs of damage due to expansive reactions in concretes incorporating natural rice husk ash when high alkalis contents are available; although not gel was found, numerous cracks and voids were observed close to unburned rice husk particles, as well as high expansions and significant decreases in strength and stiffness. In concretes with alkalis contents lower than 3 kg/m3, even with the same percentages of natural rice husk ash, there were no significant decreases in the mechanical properties.